Diazotrophic abundance and community structure associated with three meadow plants on the Qinghai-Tibet Plateau - Nshimiyimana, Jean Bosco; Zhao, Kang; Wang, Wenying; Kong, Weidong (Frontiers in Microbiology, 2024)
Symbiotic diazotrophs form associations with legumes and substantially fix nitrogen into soils. However, grasslands on the Qinghai-Tibet Plateau are dominated by non-legume plants, such as Kobresia tibetica. Herein, we investigated the diazotrophic abundance, composition, and com-munity structure in the soils and roots of three plants, non-legume K. tibetica and Kobresia hu-milis and the legume Oxytropis ochrocephala, using molecular methods targeting nifH gene. Diazotrophs were abundantly observed in both bulk and rhizosphere soils, as well as in roots of all three plants, but their abundance varied with plant type and soil. In both bulk and rhizo-sphere soils, K. tibetica showed the highest diazotroph abundance, whereas K. humilis had the lowest. In roots, O. ochrocephala and K. humilis showed the highest and the lowest diazotroph abundance, respectively. The bulk and rhizosphere soils exhibited similar diazotrophic commu-nity structure in both O. ochrocephala and K. tibetica, but were substantially distinct from the roots in both plants. Interestingly, the root diazotrophic community structures in legume O. ochrocephala and non-legume K. tibetica were similar. Diazotrophs in bulk and rhizosphere soils were more diverse than those in the roots of three plants. Rhizosphere soils of K. humilis were dominated by Actinobacteria, while rhizosphere soils and roots of K. tibetica were domi-nated by Verrumicrobia and Proteobacteria. The O. ochrocephala root diazotrophs were domi-nated by Alphaproteobacteria. These findings indicate that free-living diazotrophs abundantly and diversely occur in grassland soils dominated by non-legume plants, suggesting that these diazotrophs may play important roles in fixing nitrogen into soils on the plateau.